2013
DOI: 10.1002/lt.23765
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric liver transplantation for urea cycle disorders and organic acidemias: United Network for Organ Sharing data for 2002‐2012

Abstract: Background Decision-making about liver transplant is unique in children with urea cycle disorders (UCD) and organic acidemias (OA) because of immediate high priority on the waiting list, not related to severity of disease. There is limited national outcomes data on which to base recommendations about liver transplant for UCD or OA. Methods Retrospective analysis of UNOS data on liver recipients <18 years, transplanted 2002–12. Repeat transplants excluded. Results 5.4% of pediatric liver transplants were li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 19 publications
5
67
0
Order By: Relevance
“…23 Recent data suggest that children with organic acidemia and hyperammonemia undergoing transplant at the youngest ages have the highest risk of graft loss, which is often related to technical difficulties during surgery. 24 However, the reported increased morbidity in younger children should be considered carefully, given the limited experience of some centers with liver transplants in very small children, potentially contributing to suboptimal results. 25 Additionally, children with these rare conditions are looked after by tertiary specialists in metabolic units, often with no direct links to the transplant centers, so that the patients are proposed for liver transplant when the margins for recuperation are limited.…”
Section: Figurementioning
confidence: 99%
“…23 Recent data suggest that children with organic acidemia and hyperammonemia undergoing transplant at the youngest ages have the highest risk of graft loss, which is often related to technical difficulties during surgery. 24 However, the reported increased morbidity in younger children should be considered carefully, given the limited experience of some centers with liver transplants in very small children, potentially contributing to suboptimal results. 25 Additionally, children with these rare conditions are looked after by tertiary specialists in metabolic units, often with no direct links to the transplant centers, so that the patients are proposed for liver transplant when the margins for recuperation are limited.…”
Section: Figurementioning
confidence: 99%
“…3 However, the United Network for Organ Sharing data have suggested that patients at the youngest ages appear to have the highest graft morbidity due to difficult vascular anastomoses and consequent thrombosis. 4 Our 6.5-year-old patient (who received a liver transplant at the age of 2 years) had hepatic artery thrombosis, which was treated with angiography, intra-arterial tissue plasminogen activator infusion, and subsequent hepatic artery reanastomosis. The optimal timing of liver transplant for young patients remains unclear.…”
Section: Discussionmentioning
confidence: 98%
“…3 As shown in several studies, 5-year survival rates are greater than 85% with transplant. [4][5][6] Liver transplant during the first few months of life may prevent neurologic deficits in severe cases. However, transplant at early ages also may increase the risk of perioperative and postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…Argininosuccinic aciduria is the only urea cycle disorder in which liver fibrosis can develop as a late complication. 5,6,8,9 The number of cases in which LT has been performed for urea cycle disorders is limited.…”
Section: Figure 1 Urea Cyclementioning
confidence: 99%